PKM PENGEMBANGAN KURIKULUM BERBASIS SERTIFIKASI INTERNASIONAL UNTUK SMK KABUPATEN MALANG - Akhriza, Tubagus; Arifin, Samsul; Syaifulloh, Ali (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
This article is written based on the results of the realization of community engagement grants under the Community Partnership Program (PKM) scheme received by the PKM team of Pradnya Paramita School of Informatics Management and Computer (STIMATA) Malang for the 2018 realization year. The theme selected was about the development of an international certification-based curriculum for Malang District Vocational Senior High Schools (SMK), where two SMKs that become partners are multimedia majors of SMK Diponegoro Tumpang and software engineering majors of SMK Riyadlul Qur'an Ngajum Kepanjen. The motivation of the proposed activity is the desire of the partners to improve the quality of the curriculum so their graduates are ready and able to pass the competency certification exam issued by international information technology (IT) vendors. STIMATA as an IT-based campus proposed a solution for this problem by developing the curriculum for SMK based on Microsoft Technology Associate (MTA) – software development fundamental certification for SMK Riyadlul Qur'an and Adobe Certified Associate (ACA) video communication certification with Adobe Premier for SMK Diponegoro. With an international certification-based curriculum, it is expected that the readiness and competitiveness of SMK’s graduates in global job market are improving as well, and the transformation of science and technology from university to the social community is undergoing well